KERANGKA ADVOKASI KEBIJAKAN PENCEGAHAN PENYALAH-GUNAAN NARKOTIKA PADA GENERASI MUDA: (Model Intervensi Program Melalui Kurikulum Untuk Kelompok Mahasiswa Di Kota Bengkulu) - Dhamarjanty, Fuji; Alexsander, Alexsander; Harmiati, Harmiati; Sutardi, Dodo; Sakti, Budiman; Putra, Bobby Mandala; Ariyanto, Ariyanto; Marloanto, Nuche (Faculty of Social and Political Sciences Universitas Prof Dr Hazairin, SH, 2022)
The research aims to answer the problem of the conditions, problems, and objectives of the drug abuse prevention policy among students in the city of Bengkulu. The framework adopted by the program advocacy model consists of activities; mapping conditions and constraints, looking for leverage points, and developing accepted policy objectives (Young and Quinn, 2012). The exploratory qualitative research method is a phenomenological approach. The unit of analysis is a group of students, lecturers, policy practitioners (Provincial BNN, counselors, rehabilitants, police,) and the community. Research informants were taken as many as 25 people. The research was carried out in September-October 2022 in Bengkulu by collecting data through FGDs. Interview and literature study. Triangulation (source, time, actors) was carried out to test the validity-reliability of the data and data analysis was carried out in an interactive process. The results of the study show that micro-policy support will be provided by universities such as constructing an education/teaching program that can leverage the success of the Movement to Prevent Narcotics Abuse among College Students. The implication is social policy where the anti-drug education policy model needs to be implemented in the movement to prevent drug abuse